2006
DOI: 10.1158/0008-5472.can-05-3416
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl and Geranylgeranyl Transferase Inhibitors Induce G1 Arrest by Targeting the Proteasome

Abstract: Isoprenoid inhibitors are being evaluated as agents for the treatment of cancer. Their antitumor activity is attributed to inhibition of post-translational modification of Ras, which is crucial for its translocation and attachment to the plasma membrane, and ultimate involvement in signal transduction. However, whether blocking of Ras is solely responsible for the observed antitumor activity is unresolved. In this report, we propose an alternate mechanism. Using breast tumor models, we show that agents possess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 43 publications
4
30
1
Order By: Relevance
“…Gene expression in different prostate cancer cell lines is so complex; thus, lovastatin and simvastatin can trigger more apoptosis in one tumor cell line (e.g., LnCaP) but induce both apoptosis and growth arrest in others (PC3 and Du145). Previous studies showed that statins induced different tumor cells to undergo apoptosis by activating caspase-8 or that they induced tumor cell growth arrest at G 1 phase by inducing p21 (28)(29)(30). We observed both phenomena.…”
Section: Discussionsupporting
confidence: 72%
“…Gene expression in different prostate cancer cell lines is so complex; thus, lovastatin and simvastatin can trigger more apoptosis in one tumor cell line (e.g., LnCaP) but induce both apoptosis and growth arrest in others (PC3 and Du145). Previous studies showed that statins induced different tumor cells to undergo apoptosis by activating caspase-8 or that they induced tumor cell growth arrest at G 1 phase by inducing p21 (28)(29)(30). We observed both phenomena.…”
Section: Discussionsupporting
confidence: 72%
“…The concentration-dependent effect on G 0 /G 1 arrest in promastigotes was largely at the expense of S-phase cells, with low changes in the G 2 /M-phase cell population compared with the untreated pro-mastigotes. The drug-induced cell cycle perturbations, such as an increase in the number of cells in the G 1 phase, have been reported to correlate with a response to chemotherapy (43).…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that a mild reduction of Rap1 signaling could rescue the proper localization of N-Cad and Cx43 at the cell surface. To test this idea, Mex3b was silenced in TM4 cells and exposed to the Rap1 inhibitor GGTI-298 (Efuet and Keyomarsi, 2006). Analysis of Rap1-GTP levels by pulldown confirmed the partial inhibition of Rap1 activity after 30 min of exposure to 12.5 μM GGTI (supplementary material Fig.…”
Section: Mex3b Regulates the Activity And The Spatial Localization Ofmentioning
confidence: 99%